ANALYSIS OF THE LOCAL BUDGETING POLICY ACCOUNTABILITY IN SOUTH TANGERANG CITY BANTEN PROVINCE - Siti Aisyah (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
Study on the accountability of the budget policy area is an important issue in the development of the science of government. It concerns the relationship between the governing and the governed in countries that embrace democratic framework. Analysis of budgetary policy accountability with regard to the ability of the government in the answer and explain to the people how the government's performance is done, which is manifested in the form of government activities that costs of the money that comes from the people, carried out fairly and based on the ethics. Based on the identification of issues, there are research problems of accountability in budget policy area in South Tangerang City, Banten Province. The purpose of this study was to analyze the accountability of budget policy in South Tangerang City, Banten Province. This study was a qualitative study. The research data is limited to data related to the expenditure in 2011-2016. Data were collected through interviews to informants in relation to problems of research and collection of secondary data that support this research. The analysis focused on the performance of the local government, the achievement of accountability of budgetary policy and strategies in achieving accountability. Based on the analysis, the study found The Local Governance Scorecard Model (LGSC), the importance of improving the elements related to the achievement of budgetary policy accountability, as well as the strategies are needed to improve accountability in South Tangerang City, Banten Province. The theoretical implications of the research findings in the development of the science of governance are the importance of developing a balanced of the local government performance concept, upholding ethical governance as a guideline in behaving and acting for apparatus, as well as openness in governance.